Student Self-Formation in International Education - Marginson, Simon (Journal of studies in international education, 2014)
In research in cross-cultural psychology, international education is largely understood as an "adjustment" to host country norms and institutions, a notion that prioritizes social order and stability. The student is seen as in deficit in relation to these norms. The student's home country identity becomes seen as a barrier to be broken down. In contrast, this article sees higher education, and within that international education, as a process of self-formation within conditions of disequilibrium in which student subjects manage their lives reflexively, fashioning their own changing identities, albeit under social circumstances largely beyond their control. International students form their self-trajectories somewhere between home country identity (which continues to evolve in the country of education), host country identity, and a larger set of cosmopolitan options. In piloting their pathways they draw on multiple identities and fashion new forms of hybrid identity. The article highlights the need for international education programs to strengthen the agency freedom of students, and its scope and resources, to facilitate this educational process of self-formation. (HoF/text adopted).